2015
DOI: 10.1007/s00442-015-3522-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of potential factors allowing coexistence in a sexual/asexual minnow complex

Abstract: The northern redbelly dace (Chrosomus eos) and the finescale dace (C. neogaeus) have hybridized to produce an all-female, asexual hybrid (C. eos-neogaeus) that reproduces by sperm-limited parthenogenesis (gynogenesis). However, in this system, gynogenesis is not 100 % efficient; triploid females are occasionally formed which reproduce as sexuals, producing nuclear males and females of the paternal species (generally C. eos). Thus, the asexual lineage continually produces occasional males that can serve as a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…These empirical results strongly contrast with the expectations of Barron et al. 's theoretical model (). Under their model, an abundance of hybrids allowing the formation of cybrids as low as 5% is expected to generate high amount of cybrids, leading the sympatric wild type to extinction (Barron et al., ).…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…These empirical results strongly contrast with the expectations of Barron et al. 's theoretical model (). Under their model, an abundance of hybrids allowing the formation of cybrids as low as 5% is expected to generate high amount of cybrids, leading the sympatric wild type to extinction (Barron et al., ).…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, de novo production of cybrids is not only dependent on the presence of hybrids, as proposed by Barron et al. (), but also other factors, such as genetic, ecological, and environmental conditions, may hinder the efficiency of cybrid production.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, according to Barron et al. 's () theoretical model, the systematic production of cybrids by triploid individuals, even if the proportion of triploid is as less as 5%, would result in the total replacement of the ancestral sexual C. eos populations. However, previous studies reported the presence of C. eos in sympatry with gynogenetic and cybrid individuals in various natural populations throughout the C. eos‐neogaeus distribution (Angers & Schlosser, ; Mee & Taylor, ; Vergilino et al., ).…”
Section: Discussionmentioning
confidence: 99%